Social Media Use by Infopreneurs during the COVID-19 Pandemic in Osun State, Nigeria - Ajiboye, Olubukola Oluyemisi; Chris-Israel, Helen Osebequen (Communicate: Journal of Library and Information Science, 2023)
The study investigated the use of social media marketing strategies among infopreneurs in Osun State, Nigeria during the COVID-19 Pandemic. The aim of this study was to investigate the effect of social media marketing strategies on the businesses of infopreneurs during the COVID-19 pandemic. Four research questions guided the study. The study adopted a survey research design and online survey form was used as instrument for data collection. The population of the study comprised all the members of the Nigeria Library Association in Osun State in Nigeria and convenience sampling was used to sample 38 infopreneurs. This was largely due to the fact that lockdown banned activities across the states and the only way they could be reached was online. The study showed that there was a marked difference in the impact of social media on the businesses of infopreneurs before and during the COVID-19 pandemic. The study also showed that infopreneurs do not possess adequate knowledge of the dynamics of social media that will assist them in increasing sales in their businesses. The study recommended that infopreneurs should transcend beyond personal development in acquiring knowledge of social media and exploit avenues of training that will equip them with the necessary practical skills to drive and increase sales in their businesses.